2006
DOI: 10.1109/tvlsi.2006.874355
|View full text |Cite
|
Sign up to set email alerts
|

Combined time and information redundancy for SEU-tolerance in energy-efficient real-time systems

Abstract: Abstract-Recently the trade-off between energy consumption and fault-tolerance in real-time systems has been highlighted. These works have focused on dynamic voltage scaling (DVS) to reduce dynamic energy dissipation and on time redundancy to achieve transient-fault tolerance. While the time redundancy technique exploits the available slack time to increase the faulttolerance by performing recovery executions, DVS exploits slack time to save energy. Therefore we believe there is a resource conflict between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…In the related literature, various implementations of time-redundancy systems have been considered (e.g., [1][2] [3][5] [6]). These various implementations differ in energy management technique, recovery execution policy, and slack time management.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the related literature, various implementations of time-redundancy systems have been considered (e.g., [1][2] [3][5] [6]). These various implementations differ in energy management technique, recovery execution policy, and slack time management.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Note that, as discussed in Section II, here we focus only on transient faults. The occurrence of transient faults in digital systems usually follows a Poisson process [6][7] [29]. It has been observed that in DVS-enabled systems the rate of transient faults increases exponentially as the supply voltage decreases, so that the fault rate can be expressed as [32]: …”
Section: Reliability Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Al-Omari et al proposed a technique to handle a single error in multiprocessor systems while ensuring timing constraints, and Izosimov et al proposed for hard real-time safetycritical applications the optimization of re-execution and roll-back recovery under the assumption that errors are detected and that the maximal number of faults are known [8]. Ejlali et al explore the resource conflict between timeredundancy and dynamic voltage scaling [9] and Cai et al study fault-tolerant cache design [10].…”
Section: Introductionmentioning
confidence: 99%